Effect of celecoxib and paracetamol on the functional state of the central nervous system, pain sensitivity, and physical endurance of rats with acute heat injury - P.O. Chuikova; S.Yu. Shtrygol’ (Medičnì Perspektivi)
Acute heat injury (AHI) is a serious condition caused by an excessive increase in body temperature, usually due to prolonged exposure to high environmental temperatures or intense physical activity in the heat. Without timely treatment, heat stroke can lead to severe damage to the central nervous system with cerebral edema, profound disturbances in the water-salt balance and internal organs, coma and death. Since the effectiveness of drugs for the treatment of thermal injuries has not been proven, the search for new thermoprotective agents with different mechanisms of action, in particular inhibitors of the arachidonic acid cascade, is urgent. In a preliminary screening study on the AHI model in rats, it was found that among cyclooxygenase (COX) inhibitors, the highly selective COX-2 inhibitor celecoxib and the analgesic-antipyretic paracetamol are the most effective in preventing hyperthermia and improving the course of the recovery period. The purpose of this study was to determine the impact of the specified screening leaders on the functional state of the central nervous system, pain sensitivity and physical endurance in the recovery period of heat injury. The AHI model was reproduced on adult white male rats according to the previously proposed and validated method by means of a 30-minute exposure at +55°C. Animals were divided into 4 groups with 8 rats in each group: intact control, control pathology, paracetamol group and celecoxib group. Based on the results of the study, it was established that celecoxib exhibits a pronounced thermoprotective effect, probably improves the state of the central nervous system in terms of behavioral reactions and physical endurance of animals in the recovery period after acute heat injury. At the same time, paracetamol after acute heat injury does not have a distinct positive effect on the functional state of the central nervous system, moderately improves the physical endurance of rats and is inferior to celecoxib in all the studied parameters. These results open new opportunities for the development of approaches to the treatment of AHI and confirm the different effectiveness of the use of celecoxib and paracetamol in thermal injuries.